A qualitative study on the psychological experience of caregivers of COVID-19 patients - Sun, Niuniu; Wei, Luoqun; Shi, Suling; Jiao, Dandan; Song, Runluo; Ma, Lili; Wang, Hongwei; Wang, Chao; Wang, Zhaoguo; You, Yanli; Liu, Shuhua; Wang, Hongyun (American journal of infection control, 2020)
•Studies on the psychological experience of nurses combating COVID-19 are lacking.•We investigated the psychological experience of caregivers of COVID-19 patients.•Nurses showed interweaving positive/negative emotions during outbreak of COVID-19.•Negative emotions are dominant in the early stages of the COVID-19 outbreak.•Coping styles and psychological growth are important for maintaining mental health. The coronavirus disease 2019 (COVID-19) is spreading rapidly, bringing pressure and challenges to nursing staff. To explore the psychology of nurses caring for COVID-19 patients. Using a phenomenological approach, we enrolled 20 nurses who provided care for COVID-19 patients in the First Affiliated Hospital of Henan University of Science and Technology from January 20, to February 10, 2020. The interviews were conducted face-to-face or by telephone and were analysed by Colaizzi's 7-step method. The psychological experience of nurses caring for COVID-19 patients can be summarized into 4 themes. First, negative emotions present in early stage consisting of fatigue, discomfort, and helplessness was caused by high-intensity work, fear and anxiety, and concern for patients and family members. Second, self-coping styles included psychological and life adjustment, altruistic acts, team support, and rational cognition. Third, we found growth under pressure, which included increased affection and gratefulness, development of professional responsibility, and self-reflection. Finally, we showed that positive emotions occurred simultaneously with negative emotions. During an epidemic outbreak, positive and negative emotions of the front-line nurses interweaved and coexisted. In the early stage, negative emotions were dominant and positive emotions appeared gradually. Self-coping styles and psychological growth played an important role in maintaining mental health of nurses.